Pengaruh Biaya Operasi Dan Penjualan Terhadap Pengembalian Aset Pada Sub Sektor Perusahaan Manufaktur Makanan Dan Minuman Terdaftar Di BEI Periode 2015-2019 - Cindy Luthfiyani Vinsalia; Nanu Hasanuh (COSTING : Journal of Economic, Business and Accounting, 2021)
This study aims to determine and examine the effect of operating costs and sales both partially and jointly on Return On Asset in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the period 2015-2019. The research population includes all food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the 2015-2019 period. The sample was determined by purposive sampling. The data analysis technique in this research is descriptive verification. Hypothesis testing using multiple linear regression analysis model. This study uses the SPSS version 23 program to process data. The results showed that partially operational costs have a significant effect on return on assets, sales have no significant effect on return on assets. Meanwhile, simultaneously, operating costs and sales have a significant effect on return on assets. Keywords: Operational Costs, Sales, Return On Assets